Body Mass Index, a Body Shape Index, and Waist-to-Height Ratio in Predicting Elevated Blood Pressure - Bryan Junius Winata; Veronika Maria Sidharta; Linawati Hananta; Vetinly Vetinly; Nawanto Agung Prastowo (Althea Medical Journal, 2022)
Background: One of the complications of obesity is an elevation in blood pressure  which can increase the risk of hypertension. This study aimed to explore body mass index (BMI), a body shape index (ABSI), and waist-to-height ratio (WHtR) in predicting elevated blood pressure (BP).Methods: This study was conducted in a cross-sectional design on 215 medical students from October 2019 to September 2020. Respondents measured their own weight, height, waist circumference and BP. Receiver operating characteristics (ROC) curve were analyzed using IBM SPSS v.23. Results: Of the 215 medical students who participated in this study, only 102 met the inclusion criteria. The majority of the students were female (n=71, 69.6%) with a mean age of 19.37 years, and normal blood pressure (n=90, 88.2%). Area under the ROC curve (AUC) of WHtR and ABSI were 0.774 (p-value= 0.002) and 0.766 (p-value= 0.003) respectively, which were still acceptable. However, the AUC of BMI (p-value=0.589) was 0.11, which was considered poor.Conclusion: The indicators of obesity can be used as a screening value for increased blood pressure in adults, with BMI being the weakest indicator compared to ABSI and WHtR. Further research is needed to examine ABSI and WHtR indicators as predictor of increased blood pressure in adults.